Women, Leadership, and Mosques - Krista Riley (International Institute of Islamic Thought, 2014)
Edited by Masooda Bano and Hilary Kalmbach, Women, Leadership, and Mosques: Changes in Contemporary Islamic Authority is a compilation of papers presented at a 2009 conference of the same name. The book’s twenty chapters represent a diverse range of geographic, thematic, and methodological approaches to questions of female leadership within mosques, religious scholarship, education, Muslim organizations, and other Islamic spaces. Together, they paint a rich and complex picture of the intersections of gender, religion, culture, history, politics, class, and migration, as well as the impact of these intersections on female authority in Islamic contexts. In their introduction to the first of the book’s three sections, the editors describe the section’s chapters as reflecting the impact of “male invitation, state intervention, and female initiative” (p. 31) on women’s leadership roles. The first chapter, by Maria Jaschok, looks at female ahong (imams) in women’s mosques in China, who provide religious education, counselling, and prayer leadership in gender-segregated spaces. She discusses the complex debates about segregation, empowerment, and religious innovation (bid‘ah) that these mosques represent. The second chapter, by Margaret J. Rausch, examines the context of Morocco’s murshidahs, women trained and certified by the Moroccan government as preachers, teachers, and counsellors, and who have an important influence on women’s religious education and mosque ...